The Influence of Equity Incentive and its Concentration Degree on Enterprise Investment Efficiency - Sun, Yuxin (Transactions on Economics, Business and Management Research, 2023)
As an important part of China’s modern industrial system, high-tech industry has long-term inefficient investment problems due to the characteristics of high investment demand, high risk and long cycle. As an incentive and constraint mechanism based on the principal-agent theory, equity incentive can effectively reduce the agency cost and improve the investment efficiency of enterprises. Based on the different perspective of equity incentive between senior executives and core technical personnel, this paper takes the sample of equity incentive in 2018-2022 to test the impact of equity incentive on the investment efficiency of enterprises. The results show that equity incentive can effectively improve the investment efficiency, alleviate the investment shortage and restrain the excessive investment; equity concentration plays a negative effect on the relationship between equity incentive and enterprise investment efficiency; compared with executive equity incentives, core technical personnel equity incentives have a more significant effect on improving investment efficiency, Therefore, enterprises should pay attention to improving the level of equity incentive; focus on the influence of equity structure on the utility of equity incentive and prevent excessive equity concentration; when designing equity incentive plans, focus on incentivizing core technical personnel.